Low temperature crystallization of SrBi2Ta2O9 thin films using microwave oven - Zanetti, S. M.; Vasconcelos, J. S.; Vasconcelos, NSLS; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
SrBi2Ta2O9 thin films, produced by the polymeric precursor method, were crystallized at low temperature using a domestic microwave oven. A SiC susceptor were used to absorb the microwave energy and rapidly transfer the heat to the film. Low microwave power and short time have been used. The films thus obtained are crack-free, well-adhered, and fully crystallized, even when treated at 600 degreesC for 10 min. The microstructure displayed a polycrystalline nature with an elongate grain size comparable to the films obtained by the conventional treatment. The dielectric constant values are 240, 159 and 67, for the films treated at 600 degreesC, 650 degreesC and 700 degreesC, respectively, when the films are placed directly on the SiC susceptor. Electrical measurements revealed that the increase of the temperature treatment to 700 degreesC causes a complete loss of ferroelectricity due to degradation of the bottom interface. A 4 nun-ceramic wool put between the susceptor and the substrate minimizes the interface degradation leading to a dielectric constant, a dielectric loss, and a remnant polarization (2P(r)) of 181 muC/cm(2), 0.032 muC/cm(2), and 12.8 muC/cm(2), respectively, for a film treated at 750 degreesC for 20 min. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: SrBi2Ta2O9; SBT; thin film; ferroelectric; microwave; crystallization